2000
DOI: 10.1034/j.1600-0749.13.s8.20.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Vesicular Trafficking of Tyrosinase Gene Family Protein in Eu‐ and Pheomelanosome Biogenesis

Abstract: The intracellular vesicular trafficking in the melanosome biogenesis (melanogenesis) is reviewed with the incorporation of our own experimental findings. The melanosome biogenesis involves four stages of melanosome maturation, which reflect the transport of structural and enzymatic proteins from Golgi (trans-Golgi network: TGN) to the melanosomal compartment and their organization therein. The major melanosomal proteins include tyrosinase gene family protein (tyrosinase and tyrosinase-related protein; TRP), ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
0
41
0
3
Order By: Relevance
“…Lysosomal enzymes are ultimately delivered to lysosomes either by maturation of the prelysosomes or vesicular transport to or fusion with pre-existing lysosomes (Mullock et al, 1998;Karlsson et al, 1998). It has been recently indicated that membrane proteins are targeted to lysosomes and melanosomes using the same or similar targeting motif, i.e., tyrosine-or di-leucine-based motifs, respectively (Vijayasaradhi et al, 1995;Jimbow et al, 2000a). Calvo et al (1999) characterized sorting determinants of tyrosinase, and found, using HeLa cells, that the cytoplasmic domain of tyrosinase was necessary not only for internalization to but also for its steady-state localization in late endosomes and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysosomal enzymes are ultimately delivered to lysosomes either by maturation of the prelysosomes or vesicular transport to or fusion with pre-existing lysosomes (Mullock et al, 1998;Karlsson et al, 1998). It has been recently indicated that membrane proteins are targeted to lysosomes and melanosomes using the same or similar targeting motif, i.e., tyrosine-or di-leucine-based motifs, respectively (Vijayasaradhi et al, 1995;Jimbow et al, 2000a). Calvo et al (1999) characterized sorting determinants of tyrosinase, and found, using HeLa cells, that the cytoplasmic domain of tyrosinase was necessary not only for internalization to but also for its steady-state localization in late endosomes and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase family protein is glycosylated and assembled in the ER with the help of a molecular chaperone, calnexin (Toyofuku et al, 1999). It is then transported from the trans-Golgi network (TGN) to melanosomes through intracellular transport vesicles (Jimbow et al, 2000a). Our recent studies as well as those of others indicate that a number of intracellular transporters are involved in this melanogenesis cascade, including adaptor protein (AP3), a number of small guanosine triphosphate-binding proteins, including rab7, and phosphoinositide 3 kinase (Jimbow et al, 2000b).…”
mentioning
confidence: 99%
“…In contrast, in those melanosomes in which there is synthesis of pheomelanin only material with grain aspect is observed in all the maturation phases. (Jimbow et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As unidades epidérmico-melânicas são formadas pela associação de melanócitos e queratinócitos na proporção de 1:30. O número de melanócitos/mm 2 é em torno de dois mil nas áreas mais expostas ao UV e cerca de mil no restante do corpo (Jimbow et al, 2000). Os diferentes tons de pele e pelos não dependem do número de melanócitos, mas sim, do grau da atividade de síntese da melanina e da proporção entre eumelanina e feumelanina sintetizada (Jimbow et al, 2000;Jones et al, 2002).…”
Section: Melanogêneseunclassified
“…Os diferentes tons de pele e pelos não dependem do número de melanócitos, mas sim, do grau da atividade de síntese da melanina e da proporção entre eumelanina e feumelanina sintetizada (Jimbow et al, 2000;Jones et al, 2002). Figura 6: Disposição dos melanócitos na epiderme A síntese da melanina é restrita ao melanossomas contidos nos citoplasmas dos melanócitos (Miranda e Botti, 1983;Jimbow et al, 2000;Jimbow K, 2000), e é iniciada pela hidroxilação da tirosina pela ação da tirosina hidroxilase, formando a DOPA, sendo oxidada pela DOPAquinase formando a DOPAquinona (PHILIPPSEN, 2006;KORMOS et al, 2010). A DOPAquinona é um intermediário altamente reativo, que na ausência de compostos tióis sofre ciclização, levando à produção de eumelanina, de cor preta ou marrom.…”
Section: Melanogêneseunclassified